A CONCEPTUAL MODEL FOR DESIGNING TEACHER-CENTERED PROFESSIONAL DEVELOPMENT : Received: 14th March 2024 Revised: 11th April 2024, 29th April 2024 & 30th April 2024 Accepted: 1st April 2024 - Francheska D. Starks, (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Educators often experience significant levels of stress in the workplace that impact their enthusiasm about the profession and longevity in the field of education. Some personal impacts of stress on educators may include emotional numbing, feeling shut down, loss of energy, and increased illness or fatigue. Recently, some schools and districts have begun investing in programming to support educator well-being; however, these initiatives are rarely developed and co-led by educators themselves, and they do not address systemic issues within schools that may serve as barriers to teachers’ well-being. In this paper we draw upon existing theories and research, Critical Professional Engagement, Healing-Centered Engagement, and Critical Love Praxis, to explore the development and use of a conceptual framework to support the design of teacher-centered and justice-oriented professional development.